Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/3276148
|View full text |Cite
|
Sign up to set email alerts
|

MitoQ Modulates Lipopolysaccharide-Induced Intestinal Barrier Dysfunction via Regulating Nrf2 Signaling

Abstract: Background. Gut barrier dysfunction with alterant mucosal permeability during sepsis is a challenge problem in clinical practice. Intestinal epithelial cells (IECs) are strongly involved in mucosal oxidative stress and inflammatory response. The current study aimed at investigating the effect of MitoQ, a mitochondrial targeted antioxidant, in the treatment of intestinal injury and its potential mechanism during sepsis. Methods. 30 minutes before sepsis induction by lipopolysaccharide (LPS) treatment, mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
(29 reference statements)
4
23
0
Order By: Relevance
“…Furthermore, the elevation of Nrf2 in cytoplasm induced by As 2 O 3 was further significantly enhanced by lncRNA OTUD6B-AS1; however, Nrf2 in the nucleus showed the opposite trend. This discovery was consistent with Li et al's report [ 37 ] and Zhang et al's study [ 38 ]. A marked increase in the generation of ROS exceeds the physiological capacity of SOD and GSH-Px, and the exhaustion of these enzymes reduces their activity, ultimately leading to oxidative damage.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the elevation of Nrf2 in cytoplasm induced by As 2 O 3 was further significantly enhanced by lncRNA OTUD6B-AS1; however, Nrf2 in the nucleus showed the opposite trend. This discovery was consistent with Li et al's report [ 37 ] and Zhang et al's study [ 38 ]. A marked increase in the generation of ROS exceeds the physiological capacity of SOD and GSH-Px, and the exhaustion of these enzymes reduces their activity, ultimately leading to oxidative damage.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, injection of an equivalent dose of R. sphaeroides LPS did not alter blood plasma FITC compared to saline injected mice (Fig 3c). Bacteria produce the majority of circulating D-lactate, and elevated blood D-lactate is a surrogate marker of increased intestinal permeability (Liu et al, 2016;Zhang et al, 2020). We found that only E. coli LPS, but not LPS from R. sphaeroides, increased levels of blood plasma D-lactate (Fig 3d).…”
Section: Resultssupporting
confidence: 52%
“…SOD catalyzes the conversion of superoxide to hydrogen peroxide, which, in turn, is converted to water by glutathione peroxidase (GPx). Under oxidative stress, the expression of antioxidant genes is activated by translocation of nuclear factor E2-related factor 2 (Nrf2) from the cytoplasm to the nucleus [ 11 , 58 ].…”
Section: Generation Of Mtros and Their Role In Normal And Pathologmentioning
confidence: 99%
“…The impairment of gut permeability is a serious consequence of dysbiosis. MitoQ has been shown to improve intestinal permeability and inhibit LPS-induced bacterial translocation via a decrease in oxidative stress and restoration of the level of tight junction proteins (occludin and ZO-1) in the gut epithelium [ 11 ]. The authors showed that MitoQ alleviates LPS-induced oxidative stress in intestinal epithelial cells, triggering the nuclear translocation of the nuclear factor Nrf2, which, in turn, stimulates the expression of its downstream antioxidant genes [ 11 ].…”
Section: Mitochondria-targeted Antioxidants and Their Application mentioning
confidence: 99%
See 1 more Smart Citation